Poverty and Charity in the Jewish Community of Medieval Egypt - Cohen, Mark R., 1943- (Book collections on Project MUSE., 2005)
What was it like to be poor in the Middle Ages? In the past, the answer to this question came only from institutions and individuals who gave relief to the less fortunate. This book, by one of the top scholars in the field, is the first comprehensive book to study poverty in a premodern Jewish community--from the viewpoint of both the poor and those who provided for them. Mark Cohen mines the richest body of documents available on the matter: the papers of the Cairo Geniza. These documents, located in the Geniza, a hidden chamber for discarded papers situated in a medieval synagogue in Old Cai.